1972
DOI: 10.1111/j.1365-2389.1972.tb01668.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Cultivation on the Structure and Other Physical Characteristics of Grassland and Arable Soils (194–970)

Abstract: WITH 3 PLATES SummaryCultivating grassland changes the physical state of the soil. The paper describes observations and measurements made in the field and the laboratory on a wide range of soils (with series names) in England over a period of 25 years. D y Journal of Soil Science, Vol. 23, No. 4, 1972 6113.5.3 c c 364 A. J. LOW All single-property measurements give only a limited assessment of the physical state of a soil. Soils can be assessed satisfactorily only by making a range of measurements appropriate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
36
0
1

Year Published

1973
1973
2008
2008

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 129 publications
(39 citation statements)
references
References 14 publications
2
36
0
1
Order By: Relevance
“…Therefore, even if afforestation only slightly affects soil C stocks at the local level, it could have a significant effect on the global C budget if enough agricultural land is converted (Low 1972;de Jong 1981;Elliott 1986;Janzen 1987; Monreal et al1995). Following afforestation, changes inevitably occur in the quality, quantity, timing, and spatial distribution of soil C inputs (Paul et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, even if afforestation only slightly affects soil C stocks at the local level, it could have a significant effect on the global C budget if enough agricultural land is converted (Low 1972;de Jong 1981;Elliott 1986;Janzen 1987; Monreal et al1995). Following afforestation, changes inevitably occur in the quality, quantity, timing, and spatial distribution of soil C inputs (Paul et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…In this experiment, the number of earthworms in the PA treatment was as low as 12% of the number in the PG treatment. Low (1972) reported that after 25 years of regular cultivation, the numbers of earthworms were only 11-16% of those in old grassland. Edwards and Bohlen (1996) mention two reasons for a decreased number of earthworms, besides the mechanical damage and predation after cultivation, the …”
Section: Earthwormsmentioning
confidence: 99%
“…This approach has been used by Angers et al (1987), and Baldock and Kay (1987) (Low 1955;Greacen 1958 Low (1955) and Greacen (1958) (Low 1972).…”
mentioning
confidence: 99%